PENGARUH LINGKUNGAN KERJA, KOMPENSASI FINANSIAL DAN SEMANGAT KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. USAHA GEDUNG MANDIRI DENPASAR BALI. - Mandiyasa, Kadek Sara; Darma Yasa, I Putu Mertha; Perdanawati, Luh Putu Virra Indah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.02.TAHUN. 2021, 2021)
This study aims to determine the presence of positive and partial positive effects between the work environment, financial compensation and work morale on job satisfaction at PT. Denpasar Independent Building Enterprises. This research was conducted at PT. Denpasar Independent Building Enterprises. The technique for determining the number of samples in the study used saturated samples with a total sample of 82 employees. The results showed that 1) There was a positive influence simultaneously between the work environment, financial compensation and work morale on job satisfaction at PT. Denpasar Independent Building Enterprises. 2) There is a partially positive effect between work environment on job satisfaction at PT. Denpasar Independent Building Enterprises. 3) There is a partially positive influence between financial compensation and job satisfaction at PT. Denpasar Independent Building Enterprises. 4) There is a partially positive influence between work morale on job satisfaction at PT. Denpasar Independent Building Enterprises.